Photocatalytic efficiency improvement of Z-scheme CeO2/BiOI heterostructure for RHB degradation and benzylamine oxidation under visible light irradiation - Kanlayawat Wangkawong (2020)
© 2020 Taiwan Institute of Chemical Engineers The Z-scheme CeO2/BiOI (C/B) was prepared and evaluated for its photocatalytic RhB degradation and selective oxidation of benzylamine to N-benzylidenebenzylamine under visible light irradiation. Close contacts and chemical interactions between CeO2 and BiOI which are important for efficient charge transfer in the heterojunction were revealed by HRTEM and XPS studies. The C/B heterostructure presented nearly 1.5 and 8.0 times higher RhB degradation activity than BiOI and CeO2, respectively. The activity of C/B in oxidative coupling of benzylamine was also firstly revealed and found to be more than 2 times higher than both BiOI and CeO2. Such enhanced photocatalytic performance of the C/B is ascribed to the combined effects of extended visible-light absorption range, increased surface area and improved charge transfer efficiency as evidenced from BET, UV–vis DRS and photoelectrochemical studies. Based on XPS, UV–vis DRS, Mott-Schottky plots and active species quenching results, a Z-scheme charge transfer where photogenerated electron-hole pairs can be effectively separated is proposed for the C/B and h+ and O2●– are key active species responsible for RhB degradation and N-benzylidenebenzylamine formation. The present work highlights the enhancement of photocatalytic activity based on Z-scheme heterojunction formation and reveals a further application of photocatalysts in organic fine chemical syntheses.